THE PLACE AND SIGNIFICANCE OF INFORMATION IN THE PROCESS OF EDUCATION AND EDUCATION ("Conference on Universal Science Research 2023", 2023)
This article is about the place, importance of information in the process of education and training, and information about the information system and about the collection, transmission and processing of information about the facility that provides its employees with various information to implement its management function. data is provided.